Heart failure in pregnancy: an overview. - Ahmad, W.A.W.; Khanom, M.; Yaakob, Z.H. (Blackwell Publishing, 2011)
The treatment of heart failure in pregnant women is more difficult than in non-pregnant women, and should always involve a multidisciplinary team approach. Knowledge required includes hemodynamic changes in pregnancy and the resultant effect on women with pre-existing or pregnancy-related cardiovascular disease, cardiovascular drugs in pregnancy, ethical issues and challenges regarding saving mother and baby. In addition, women having high risk cardiac lesions should be counselled strongly against pregnancy and followed up regularly. Pregnancy with heart failure is an important issue, demanding more comprehensive studies.